EXACT SOLUTIONS OF STOCHASTIC KdV EQUATION WITH CONFORMABLE DERIVATIVES IN WHITE NOISE ENVIRONMENT - Ulutas, Esma; İnç, Mustafa; Baleanu, Dumitru (Vinca Inst Nuclear Sci, 2021)
In this article, we have considered Wick-type stochastic Korteweg de Vries (KdV) equation with conformable derivatives. By the help of white noise analysis, Hermit transform and extended G/G-expansion method, we have obtained exact travelling wave solutions of KdV equation with conformable derivatives. We have applied the inverse Hermit transform for stochastic soliton solutions and then we have shown how stochastic solutions can be presented as Brownian motion functional solutions by an application example.
Keywords: stochastic KdV equation; Wick product; conformable derivative; Hermit transforms; extended G '/G-expansion method